Karakteristik Marshall Campuran AC-WC Dengan Modifikasi Serbuk Karet Ban dan Filler Bata Merah - Muhammad Ramdhan; Ida Farida; Subhan Mulyana (Institut Teknologi Garut, 2026)
Road pavement damage often occurs faster than its planned lifespan due to the selection of inappropriate asphalt and aggregate content. The use of tire rubber powder waste and red brick powder filler is offered as an alternative modification material to improve the performance of asphalt mixtures. The study aims to evaluate the effect of varying tire rubber powder with 5% red brick powder filler on the Marshall characteristics of AC-WC mixtures. The experiments were conducted in the laboratory with reference to the 2018 Bina Marga Specifications Division 6 Asphalt Pavement. The variations in rubber powder content used were 4%, 4.5%, 5.5%, and 6% of the asphalt weight, with an optimum asphalt content of 6.3%. The results showed that the optimum rubber powder content was 4%, with all Marshall parameters meeting the 2018 Bina Marga specifications, namely stability of 1067 kg, flow of 2.47 mm, VIM of 3.28%, VMA of 15.92%, VFB of 79.94%, and MQ of 432.69 kg/mm. At levels of 4.5–6%, some parameters still met the requirements, but the VIM value exceeded the maximum limit, potentially reducing structural strength. These findings indicate the potential for practical application in extending the service life of road pavements and support the principle of sustainability through the use of industrial waste as an asphalt mixture material.